EXPLORING EFL STUDENTS’ EXPERIENCE IN TASK-BASED LANGUAGE TEACHING FOR WRITING SKILL - Aurelya, Aurelya; Pujiawati, Nia; Miftakh, Fauzi (PROJECT (Professional Journal of English Education), 2024)
This study exploring students’ experiences with task-based language teaching (TBLT) in a senior high school located in Karawang. Employing a qualitative case study design, data collection involved classroom observations during two meeting in TBLT activities and subsequent interviews with nine students. The analysis revealed a positive impact of TBLT on student experience. Students reported increased knowledge with English language use, leading to gains in vocabulary, language fluency, and writing skills. Furthermore, the study identified how TBLT made learning more active, with students participating more, working together, and figuring things out for themselves. However, challenges related to limited vocabulary knowledge and grammar difficulties were also identified. This research contributes to the field by offering insights into student perspectives on TBLT for writing skill and its influence on the overall learning process. The findings hold potential to inform educators, students, and schools on effective implementation strategies to enhance the learning experience.